Web- Based Service Search Information System (Programmer) - Syahrul Fajri; Deddy Gusman; yusnira yusnira (Journal of Engineering Science and Technology Management, 2022)
The development of information and technology today has become one of the sciences that is developing very rapidly and cannot be separated from the life of the world community for various needs, both for individuals, groups and large companies in the world. This is because of the many advantages derived from the use of information technology. Information technology is currently very important so that it can help and facilitate the work of everyday people who cannot be separated from the internet. There have been many information technologies developed in various fields as well as in the field of service ordering. It cannot be denied that there are already many applications that have been developed by developers and have been used by many people at this time